2018
DOI: 10.2147/cmar.s175596
|View full text |Cite
|
Sign up to set email alerts
|

Low periostin expression predicts poor survival in intestinal type gastric cancer patients

Abstract: Background and aimPeriostin is a protein from the Fascilin family. It is commonly present in normal tissues and is responsible for cell adhesion. Evidence has emerged showing that changes in periostin expression play an important role in tumor initiation, development, and progression. This study aims to investigate the effect of periostin in gastric cancer (GC) patients who underwent gastrectomy. Seven hundred and forty-seven GC patients who underwent gastrectomy between December 2006 and July 2011 were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In a colitis-associated colorectal cancer model using periostin-/- mice, lack of periostin expression resulted in fewer inflammatory peritoneal macrophages, as evidenced by a reduced expression of TNF-α and IL-1β, and up-regulation of TGF-β and IL-10 [ 155 ]. Interestingly, in patients with intestinal type gastric cancer, low periostin levels were associated with poor survival and lymph node metastasis [ 156 ]. The same study revealed that high periostin levels in diffuse gastric cancer was associated with high M2 macrophage infiltration, whereas this was not the case in intestinal gastric cancer.…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…In a colitis-associated colorectal cancer model using periostin-/- mice, lack of periostin expression resulted in fewer inflammatory peritoneal macrophages, as evidenced by a reduced expression of TNF-α and IL-1β, and up-regulation of TGF-β and IL-10 [ 155 ]. Interestingly, in patients with intestinal type gastric cancer, low periostin levels were associated with poor survival and lymph node metastasis [ 156 ]. The same study revealed that high periostin levels in diffuse gastric cancer was associated with high M2 macrophage infiltration, whereas this was not the case in intestinal gastric cancer.…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…DAXX expression was detected in tumor tissue and normal tissue using IHC. Tissue microarrays (TMAs) were constructed and IHC was performed on the TMA slides as described previously 22 . Briefly, the slides were incubated with mouse anti-DAXX antibodies (1:200 dilution, Santa Cruz Biotechnology, Santa Cruz, Calif., USA; sc-8043), with antibody diluent buffer used as a negative control.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…However, periostin and tenascin-C should be mentioned here, as they represent the hot topic of ECM research in cancer biology. Nevertheless, the interpretation of the findings is frequently problematic and cancer type-specific [44,45,46,47]. Particular attention is dedicated to endogenous lectins such as galectins and their relation to ECM and cancer progression [48,49].…”
Section: Tumour As a Complex Ecosystem Supporting Function Of The mentioning
confidence: 99%